Getting prepared to be surprised? Reflecting on urban planning and design in times of uncertainty - Galimberti, Beatrice; Bovo, Martina (Contesti. Città, territori, progetti, 2021)
On a radio programme at the beginning of May 2021, philosopher and psychoanalyst Romano Madera observed that although there will always be a new crisis that will sneak up on us, we can do something crucial: we can get prepared to be surprised by crises. This apparently contradictory statement, and the context it stems from, triggered a reflection on planning and radical uncertainty, and solicited us to map existing and emerging approaches that planning theory has used to address (un)known unknowns. Starting from this map and contextualising this discussion in recent responses to the COVID-19 crisis, we argue that radical uncertainty requires planning and design to move into two complementary dimensions; namely, navigating by sight through the implementation of plural approaches, and at the same time, tracing/adjusting the route, by the choice of the horizon of meaning that gives direction to our actions.